Interfacial shear, tensile strength and young modulus of kenaf fiber: the effects from different settings of alkali treatment - Hashim, Mohd Yussni; Mohd Amin, Azriszul; Marwah, Omar Mohd Faizan; Othman, Mohd Hilmi; Johar, Muhammad Akmal; Ng, Chuan Huat; Mamat, S.B. (Trans Tech Publications, 2018)
The project explained about what happened to fiber matrix interfacial shear strength, fiber tensile strength and fiber Young modulus when different alkali treatment settings were applied. Kenaf fiber were exposed to different alkali concentration, immersion duration and immersion temperature. To determine the interfacial shear strength (IFSS), unsaturated polyester matrix was utilised to expose the properties. The effects of alkali treatment on sample mechanical properties were successfully evaluated, whereby the treated sample's IFSS showed slightly higher value compared to untreated kenaf fiber at all settings. Meanwhile, the IFSS value was increased at low alkali concentration and decreased with the increment of alkali concentration percentage. On the other hand, untreated kenaf fiber tensile strength and Young modulus average value was 632MPa and 40.65GPa respectively. It was also established that the sample's tensile strength was keep reducing after treatment at all settings. At 30 minutes constant immersion duration, the percentage of kenaf fiber tensile strength decrement was 42.57% when other treatment settings increased. Furthermore, a decline pattern was obtained in term of sample tensile strength and Young modulus when the alkali treatment increased at all settings.